Systemic control of nodule formation by plant nitrogen demand requires autoregulation-dependent and independent mechanisms. (24th August 2021) - Pervent, Marjorie; Lambert, Ilana; Tauzin, Marc; Karouani, Alicia; Nigg, Martha; Jardinaud, Marie-Françoise; Severac, Dany; Colella, Stefano; Martin-Magniette, Marie-Laure; Lepetit, Marc
Abstract : Systemic control of the plant N demand on transcriptome reprogramming associated with establishment of rhizobial symbiosis involves the SUNN/CLE and additional pathways. Abstract: In legumes interacting with rhizobia, the formation of symbiotic organs involved in the acquisition of atmospheric nitrogen gas (N2 ) is dependent on the plant nitrogen (N) demand. We used Medicago truncatula plants cultivated in split-root systems to discriminate between responses to local and systemic N signaling. We evidenced a strong control of nodule formation by systemic N signaling but obtained no clear evidence of a local control by mineral nitrogen. Systemic signaling of the plant N demand controls numerous transcripts involved in root transcriptome reprogramming associated with early rhizobia interaction and nodule formation. SUPER NUMERIC NODULES (SUNN) has an important role in this control, but we found that major systemic N signaling responses remained active in the sunn mutant. Genes involved in the activation of nitrogen fixation are regulated by systemic N signaling in the mutant, explaining why its hypernodulation phenotype is not associated with higher nitrogen fixation of the whole plant. We show that the control of transcriptome reprogramming of nodule formation by systemic N signaling requires other pathway(s) that parallel the SUNN/CLE (CLAVATA3/EMBRYO SURROUNDING REGION-LIKE PEPTIDES) pathway.